COMPETENCE OR COMMUNICATION: FROM HR PROFESSIONALS TO EMPLOYEE PERFORMANCE VIA EMPLOYEE SATISFACTION - Fredson Kotamena; Pierre Senjaya; Ratna Setyowati Putri; Carter Bing Andika (Jurnal Manajemen dan Kewirausahaan, 2021)
The motivation behind this investigation was to find out the relationship between competence and communication skills of human resources professionals and employee satisfaction, as mediating variables, to improve employee performance. This study also aimed to examine the direct relationship between competence and communication skills of human resources professionals and employee performance. For data collection, a questionnaire was sent to 60 employees from the level of Section Head to Senior Manager or those directly involved in the production process and other supporting functions. The result of this study showed that the competence level of human resources professionals did not have any significant relation with employee satisfaction and employee performance. In contrast, the communication skills of human resources professionals had a significant impact on employee satisfaction and indirect correlation with employee performance; employee performance increases if employee satisfaction increases. Consequently, to be able to increase employee satisfaction, HR professionals must improve their communication skills